2022
DOI: 10.2147/tcrm.s350748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Perspectives on Cardiac Rehabilitation After Heart Failure in Elderly Patients with Frailty: A Narrative Review

Abstract: The purpose of this narrative review is to examine rehabilitation modalities for patients with heart failure and Frailty who require comprehensive intervention. Ischemic heart disease is the leading cause of death worldwide, accounting for 16% of global mortality. Due to population growing and aging, the total number of heart failure patients continues to rise, a condition known as the heart failure pandemic. Furthermore, frailty has been associated with an increased risk for heart failure and increased morbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 140 publications
0
2
0
Order By: Relevance
“… 52 This study found no significant difference in the levels of NO, NOS, SOD, and VEGF between two groups before training, while a significant improvement in two groups was found 1 year later, more obviously in the cardiac rehabilitation group, with a significant difference. It is possible that long-term cardiac rehabilitation training could increase the levels of NO and SOD in coronary artery endothelial cells, improve the endothelium-dependent vasodilatory function, promote vascular remodeling and angiogenesis, improve autonomic balance, and increase the blood flow perfusion of skeletal muscle via increasing oxygen extraction capacity, 53 which could improve myocardial ischemia-reperfusion injury, myocardioprotection, and reduce the level of VEGF. In addition, local release of NO can restrain intimal hyperplasia, down-regulate the levels of interleukin-6 and c-reactive protein significantly, reduce inflammation, and inhibit the development of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“… 52 This study found no significant difference in the levels of NO, NOS, SOD, and VEGF between two groups before training, while a significant improvement in two groups was found 1 year later, more obviously in the cardiac rehabilitation group, with a significant difference. It is possible that long-term cardiac rehabilitation training could increase the levels of NO and SOD in coronary artery endothelial cells, improve the endothelium-dependent vasodilatory function, promote vascular remodeling and angiogenesis, improve autonomic balance, and increase the blood flow perfusion of skeletal muscle via increasing oxygen extraction capacity, 53 which could improve myocardial ischemia-reperfusion injury, myocardioprotection, and reduce the level of VEGF. In addition, local release of NO can restrain intimal hyperplasia, down-regulate the levels of interleukin-6 and c-reactive protein significantly, reduce inflammation, and inhibit the development of in-stent restenosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a relationship between frailty and HF prognosis; however, interventions that improve prognosis are not yet well defined. Interventions aimed at improving the prognosis of multidomain frailty are needed [150].…”
Section: Reviewmentioning
confidence: 99%